Plastic solid waste management strategies: An overview of implications on environment and health - Sahabi Nasibatu Gada (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
Plastics are ubiquitous polymers and champions of today's environment because they are numerously useful. This paper's objective is to review different methods of plastic disposal and their impacts on health and the environment using the conceptual review method. Nowadays, anthropogenic developments and growth have increased and are resulting in progress that has led to the application of plastic in almost every aspect of human endeavors. However, today, there is an apparent mismanagement of plastic wastes ubiquitous in our environment (in land, water, and air). The methods used to handle plastic solid waste include landfilling, pulverization, open dumping, and burning or incineration. This paper basically elucidates some of the techniques used for solid waste plastic handling, merits, and demerits. Therein, headings such as plastics, microplastics in the soil, effects of incineration, effects on climate change, plastic in water, policies for correction, types of waste, and relations were elucidated. It is important to stress that plastic waste destroys the routine nature of the environment (beautiful view), alters the physical nature of the environment, causes pollution, and affects macro and microorganisms. Better methods/strategies are needed to address plastic solid waste. Plastik adalah polimer yang ada di mana-mana dan merupakan pelindung lingkungan saat ini karena banyak manfaatnya. Tujuan makalah ini adalah untuk meninjau berbagai metode pembuangan plastik dan dampaknya terhadap kesehatan dan lingkungan menggunakan metode tinjauan konseptual. Saat ini, perkembangan dan pertumbuhan antropogenik telah meningkat dan menghasilkan kemajuan yang mengarah pada penerapan plastik di hampir setiap aspek kehidupan manusia. Namun, saat ini, terdapat kesalahan pengelolaan sampah plastik yang tersebar luas di lingkungan kita (di darat, air, dan udara). Metode yang digunakan untuk menangani sampah plastik antara lain penimbunan, penghancuran, pembuangan terbuka, dan pembakaran atau insinerasi. Makalah ini pada dasarnya menjelaskan beberapa teknik yang digunakan dalam penanganan sampah plastik, kelebihan dan kekurangannya. Selain itu, dijelaskan juga mengenai plastik, mikroplastik dalam tanah, dampak pembakaran, dampak terhadap perubahan iklim, plastik dalam air, kebijakan koreksi, jenis sampah, dan hubungannya. Penting untuk dipahami bahwa sampah plastik merusak sifat rutin lingkungan (pemandangan indah), mengubah sifat fisik lingkungan, menyebabkan polusi, dan mempengaruhi makro dan mikroorganisme. Diperlukan metode/strategi yang lebih baik untuk mengatasi sampah plastik.